The Impact of Transformational Leadership and Big Data Analytics Capability on Firm Performance in FMCG Industry - Sahwa Putri Utami; Aburizal Maharsyah; Berto Mulia Wibawa; Syarifa Hanoum; Thedosia Yunita Durman (Journal of Social Research, 2025)
This study investigates the impact of transformational leadership (TL) and big data analytics capability (BDAC) on firm performance (FP) in the fast moving consumer goods (FMCG) industry in Indonesia. The research emphasizes the role of BDAC as both a direct determinant of FP and a mediator in the relationship between TL and FP. Data were collected from 118 employees of Paragon Corp using a purposive sampling technique, targeting respondents directly involved in decision making and digital transformation initiatives. Partial Least Squares–Structural Equation Modeling (PLS-SEM) was applied to analyze the data. The results reveal that TL significantly and positively influences FP, both directly and indirectly through BDAC. In addition, BDAC has a significant effect on FP and partially mediates the effect of TL on FP. These findings strengthen the Resource-Based View (RBV) by positioning leadership as a human capital resource and BDAC as a technological capability that together enhance firm competitiveness. Practically, the study provides valuable insights for companies in emerging markets to align leadership and digital analytics in order to achieve sustainable performance.